2007
DOI: 10.1039/b616882e
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of ionic liquids in micro-reactors—a process intensification study

Abstract: To date the manufacturing of ionic liquids on a large scale is limited by ineffective batch procedures employed for the alkylation step. Here we present a way to intensify the synthesis of 1-butyl-3-methylimidazolium bromide ([BMIM]Br) by using a continuously operating microreactor system. It consists of a microstructured mixer of 450 mm channel width and reaction tubes with inner diameter ranging from 2 to 6 mm allowing a production rate of 9.3 kg [BMIM]Br per day. In this reactor system the strongly exotherm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
73
2
2

Year Published

2008
2008
2019
2019

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(84 citation statements)
references
References 11 publications
6
73
2
2
Order By: Relevance
“…Typically, quaternization reactions are highly exothermic reactions. It has been reported that the heat of reaction for 1-methylimidazole and 1-bromobutane is -96 kJ mol -1 by Waterkamp et al 20 They estimated the adiabatic temperature for a run-away reaction for this system to be 48…”
Section: Reactions: Solvent or Solvent-less?mentioning
confidence: 96%
See 1 more Smart Citation
“…Typically, quaternization reactions are highly exothermic reactions. It has been reported that the heat of reaction for 1-methylimidazole and 1-bromobutane is -96 kJ mol -1 by Waterkamp et al 20 They estimated the adiabatic temperature for a run-away reaction for this system to be 48…”
Section: Reactions: Solvent or Solvent-less?mentioning
confidence: 96%
“…20 This amount of heat release can cause a number of safety concerns along with poor quality product. Burrell et al 21 investigated synthesis of larger scale quantities (~1 kg) of ILs and warn: "Caution: [this] reaction is exothermic and cooling is advisable for large scale reactions".…”
Section: Reactions: Solvent or Solvent-less?mentioning
confidence: 99%
“…Although many processes have been developed to decrease the production cost of ILs (Estager et al, 2007;Waterkamp et al, 2007) COO] did not dissolve the wood flour; however, facile extraction of the lignin was achieved. A strong inverse relationship was found between the effectiveness of cellulase-catalyzed hydrolysis of wood flour cellulose and both lignin content and cellulose crystallinity.…”
Section: Reuse Of [Emim][ch 3 Coo] To Pretreat Wood Flourmentioning
confidence: 99%
“…Waterkamp et al [60] presented a process to intensify the synthesis of 1-butyl-3-methylimidazolium bromide ([BMIM]Br) by using a continuously operating microreactor system ( Figure 7 ). The reaction unit is composed of a microstructured mixer of 450 mm channel width and with an inner diameter ranging from 2 to 6 mm, allowing a production rate of 9.3 kg [BMIM]Br per day.…”
Section: Production Of Ionic Liquidsmentioning
confidence: 99%